Enhancing Tax Compliance through Improved Tax Service Quality and the Enforcement of Tax Sanctions" - Turyana, Ruyat; Supriatiningsih, Supriatiningsih (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
This study aims to empirically examine the influence of service quality improvement and the implementation of tax sanctions on the tax compliance of individual taxpayers at KPP Pratama Jakarta Pluit. Data was collected from 96 respondents using a Convenience Sampling technique, where respondents were selected based on chance and were registered at KPP Pratama Jakarta Pluit. The data analysis used multiple linear regression analysis. The results of the study indicate that all hypotheses are supported, showing a significant impact of service quality and the enforcement of sanctions on the tax compliance of individual taxpayers at KPP Pratama Jakarta Pluit. This is influenced by the quality of human resources, good service facilities, and the enforcement of strict sanctions. The study does not differentiate between types of respondents' occupations, whether employees or entrepreneurs, and does not involve in-depth interviews, with a relatively small sample size. The findings highlight the influence of service quality and sanction enforcement on tax compliance. It is recommended that the government continue to improve service quality by enhancing the competence of tax officers, providing innovative tax service facilities, and enforcing sanctions on all non-compliant taxpayers to increase tax revenue, the benefits of which can be felt by the entire community.